Benefit of using plant growth regulators in fodder barley - Erviö, Leila; Jalli, Heikki; Kontturi, Markku; Hakkola, Heikki; Kangas, Arjo; Simojoki, Paavo (Agricultural and Food Science, 1995)
The study was conducted to investigate the effect and benefit of applying plant growth regulators (PGR) to two easily lodging barley cultivars, Arra and Kilta, which were commonly used for fodder production all over Finland. Field trials were conducted at six experimental sites in different parts of the country. Of the PGRs tested, ethephon and mepiquat/ethephon were the most effective in shortening the culm and preventing lodging. However, neither could prevent the lodge adequately in all growing circumstances. When applied at flag-leaf stage (FS 10) they increased yield under conditions favourable for lodging. They also raised the volume weight of barley, which was important for the final price of the yield. The most important factors determining future lodging of barley were an effective temperature sum of over +5°C and precipitation during the period from sowing to the beginning of tillering (FS 2). About 64-68% of the lodging risk of the cultivars studied could be predicted from weather conditions during early development of the crop. Local growing conditions and the presence of lodge had a marked impact on the results obtained with PGRs. In the case of moderate lodging the compound used determined whether a profit or loss was made on the crop. In the case of heavy lodging, compounds containing ethephon contributed to an economic return. Their application at flag-leaf stage gave a profit of FIM 70 - 390 ha-1. Since the profitability of PGR treatments depended on lodging, treatments are recommended for fodder barley only when lodging is expected. The lodging risk can be predicted within certain limits at the tillering stage of barley.